Strategic Decision Processes: Comprehensiveness and Performance in an Industry with an Unstable Environment - Fredrickson, James W.; Mitchell, Terence R. (Academy of Management Journal, 1984)
Comprehensiveness is a measure of rationality and is defined as the extent to which organizations attempt to be exhaustive or inclusive in making and integrating strategic decisions. Results from an industry with an unstable environment indicate a consistently negative relationship between comprehensiveness and performance. Limitations and extensions are discussed.